The southwestern Carpathians as an ancient centre of diversity of freshwater gammarid amphipods: insights from the Gammarus fossarum species complex - Copilaş-Ciocianu, Denis; Petrusek, Adam (Molecular ecology, 2015)
Gammarus fossarum is a diverse species complex of epigean freshwater amphipods throughout Europe. Due to their poor dispersal capabilities and ubiquity, these crustaceans may serve as a model for investigating the influence of historical factors on the contemporary distribution and diversity patterns of freshwater macrozoobenthos. Here, we investigate the fine-scale phylogeographic structure of this complex across its range in the southwestern Carpathian Mountains, which comprises two areas that are geographically isolated from its main European distribution area as well as from each other. Given the Tertiary age of many freshwater Gammarus species, we hypothesize that the southwestern Carpathian populations reflect a relict distribution pattern. We used two mitochondrial and three nuclear markers from 32 localities to reconstruct phylogenetic relationships and estimate the timings of divergence among southwestern Carpathian and non-Carpathian lineages. Cryptic diversity was evaluated from mitochondrial markers by employing phylogenetic and distance-based methods. We distinguished at least 16 cryptic microendemic taxa, some of them coexisting, distributed in the southwestern Carpathians in a mosaic-like pattern. These lineages form a monophyletic group together with several lineages from southeastern Europe. Estimated divergence times indicate a Middle Miocene origin of this clade, with many deep splits dating back to more than 10 Ma. This time frame corresponds with a period of intense geological subsidence in the region that gave birth to the Pannonian Basin. We conclude that subsidence could have been an important driver of diversification in freshwater Gammarus and that the southwestern Carpathians represent an ancient centre of diversity for these crustaceans.
Keywords: Animals; Europe; biologická evoluce; Phylogeography; DNA, Mitochondrial; modely genetické; Bayesova věta; Cell Nucleus; Evropa; Bayes Theorem; Fresh Water; Phylogeny; buněčné jádro; Amphipoda; Models, Genetic; sladká voda; fylogeografie; mitochondriální DNA; Sequence Analysis, DNA; zvířata; genetické markery; sekvenční analýza DNA; Biological Evolution; fylogeneze; Genetic Markers